STRAY CHILDREN HEALTH ASSESSMENT AND POSSIBLE WAYS OF THEIR MEDICAL RHEABILITATION IN PRESENT DAY LIFE - V.I. Oriel; V.M. Sereda (Вопросы современной педиатрии, 2006)
The article provides the analysis of statistic reports from the agencies providing stray children care in comparison with 2570 questionnaire reports collected from stray children and medical evaluation of those who were hospitalized. The article high lights medical and social features of stray children health, estimates the value of social maladaptaion risk factors and offers a model of multilevel system of rehabilitation for stray children.Key words: stray children, medical and social rehabilitation.